(untitled) - Segal, Daniel L. (Hoboken, N.J., 2006)
The chapter on evolutionary theory and the development of personality disorders is especially creative and cutting-edge. "Personality Disorders and Older Adults" should be on the bookshelf of all mental health professionals who work with ‘problem’ clients in geriatric settings, and of all academics who want to understand the latest thinking on personality and dysfunction.--Victor Molinari, University of South Florida
Keywords: Sự rối loạn nhân cách,Personality disorders in old age,Personality Disorders